THE EFFECT OF WORK QUALITY AND WORK MOTIVATION ON THE PERFORMANCE OF STATE CIVIL SERVANTS IN THE HOUSING, RESIDENTIAL AREAS AND LAND OFFICE OF KENDARI CITY - Rais, Chitra; Nur, Muh; Yuana, Indira (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The performance of Civil Servants (ASN) plays a crucial role in enhancing the quality of public services. Work motivation and work quality are often identified as key factors influencing ASN performance; However, many government agencies have yet to implement adequate policies to improve these aspects. The knowledge gap in understanding the influence of motivation and work quality on ASN performance in the public sector highlights the need for more in-depth research. This study employed a quantitative method using Partial Least Squares Structural Equation Modeling (PLS-SEM) and involved 42 ASN samples from the Department of Housing, Settlement Areas, and Land Affairs in Kendari City. The findings indicate that both work motivation and work quality significantly impact ASN performance, providing valuable insights for human resource development policies in the public sector. These results offer local governments a foundation for designing effective strategies to enhance ASN performance and provide a theoretical basis for further research on performance determinants in public service sectors.